2007
DOI: 10.1111/j.1467-7652.2007.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐level expression of secreted complex glycosylated recombinant human erythropoietin in the Physcomitrella Δ‐fuc‐t Δ‐xyl‐t mutant

Abstract: SummaryThe highly glycosylated peptide hormone erythropoietin (EPO) plays a key role in the regulation of erythrocyte maturation. Currently, marketed EPO is produced by recombinant technology in mammalian cell cultures. The complementary DNA (cDNA) for human EPO (hEPO) was transiently and stably expressed in the moss Physcomitrella patens wild-type and ∆ -fuc-t ∆ -xyl-t mutant, the latter containing N -glycans lacking the plant-specific, corebound α 1,3-fucose and β 1,2-xylose. New expression vectors were desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 48 publications
(55 reference statements)
1
86
0
3
Order By: Relevance
“…Due to the fast and precise gene manipulation technique based on homologous recombination in P. patens, the humanization of the moss glycosylation pattern is feasible and glycoengineering in moss plants is already quite advanced (reviewed in Decker et al 2014). To date, several human proteins are produced in moss, e.g., vascular endothelial growth factor (Baur et al 2005), erythropoietin (Weise et al 2007), and human complement factor H (Buettner-Mainik et al 2011). In addition, moss is used as production platform for secondary metabolites such as terpenoids (Bach et al 2014).…”
Section: Extended Moss Resources: Bioinformatics and High Throughput mentioning
confidence: 99%
“…Due to the fast and precise gene manipulation technique based on homologous recombination in P. patens, the humanization of the moss glycosylation pattern is feasible and glycoengineering in moss plants is already quite advanced (reviewed in Decker et al 2014). To date, several human proteins are produced in moss, e.g., vascular endothelial growth factor (Baur et al 2005), erythropoietin (Weise et al 2007), and human complement factor H (Buettner-Mainik et al 2011). In addition, moss is used as production platform for secondary metabolites such as terpenoids (Bach et al 2014).…”
Section: Extended Moss Resources: Bioinformatics and High Throughput mentioning
confidence: 99%
“…This is especially true for the transgene expression of proteins. Hyp residues, for example, were identified on human erythropoietin (Weise et al, 2007) and IgA1 (Karnoup et al, 2005) recombinantly expressed in Physcomitrella patens and maize (Zea mays), respectively, and Hyplinked O-glycosylation was additionally identified on IgA1, specifically in the Pro/Ser/Thr-rich hinge region where GalNAc O-glycosylation occurs in humans (Karnoup et al, 2005). More recently, Pinkhasov et al (2011) found Hyp formation (Pro-11 or Pro-12) and Hyp substituted with three arabinofuranoside residues in MUC1 TRs transiently expressed in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Разработана методика трансформации P. patens. Первым успешным примером использования этого вида мха в качестве системы экс-прессии рекомбинантных белков стало получение реком-бинантного эритропоэтина человека (Weise et al, 2007). Фирма Grenovation (Германия) разрабатывает технологию наработки биофармацевтических белков на основе P. patens в клеточной суспензионной культуре c применением биореакторов.…”
Section: актуальные технологии генетики и клеточной биологииunclassified